Modified resin composition for high-pressure-resistant and high-wear-resistant PVC (polyvinyl chloride) hose

By modifying sisal fibers and optimizing the formulation composition, a stable enhanced network structure is formed, which solves the problem of poor wear and pressure resistance of PVC hoses, and significantly improves the overall performance and processing performance of the material.

CN119529442APending Publication Date: 2025-02-28ZHEJIANG HUTIAN RUBBER BELT CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411549869.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The wear and pressure resistance of existing PVC hoses is poor, and the interface bonding strength between the filler and the PVC substrate is weak, resulting in uneven overall performance of the material.

Method used

By performing specific modification treatments on sisal fibers, including alkali treatment and interpolated modification of magnesium aluminum spinel fibers, and using long-link branch modifiers and sulfonation treatments, the formulation composition is optimized to form a stable enhanced network structure.

Benefits of technology

It significantly improves the pressure and wear resistance of PVC hoses, improves the overall performance and processing performance of the material, forms a more stable structure, improves the uniformity of pressure transmission and the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529442A_ABST
    Figure CN119529442A_ABST
Patent Text Reader

Abstract

The invention discloses a modified resin composition for a high-pressure-resistant and high-wear-resistant PVC (polyvinyl chloride) hose, and belongs to the technical field of PVC pipes. The sisal fibers are subjected to alkali treatment, impurities are removed and active sites are increased through insertion modification and alkali treatment of the magnesium aluminate spinel fibers, the magnesium aluminate spinel fibers improve the performance of the pipe due to the high length-diameter ratio and other characteristics of the magnesium aluminate spinel fibers, a stable enhanced network structure is formed in a PVC matrix, the surface hardness and wear resistance are improved, the pressure is shared, and the pressure resistance is improved. A bicyclo [2.2. 2] octane structure contained in the long-chain graft modifier disclosed by the invention has rigidity and steric hindrance effect, can uniformly disperse pressure to avoid breakage or excessive deformation of a molecular chain, and is coupled with an amino silane coupling agent to form a three-dimensional structure to improve pressure resistance and wear resistance. After sulfonic groups and a long-chain grafting modifier are introduced to the surfaces of the interspersed modified sisal fibers, the hydrophobic and oleophylic properties of the sisal fibers are improved, the compatibility with PVC is enhanced, agglomeration is avoided, friction is effectively resisted, and the processing fluidity of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC pipes, and in particular relates to a modified resin composition for a high-pressure-resistant and high-wear-resistant PVC hose. Background Art

[0002] In the field of polymer materials, polyvinyl chloride (PVC), as an important synthetic material, is widely used in industrial production and daily life due to its unique molecular structure and performance characteristics. PVC hose is a flexible pipe made by mixing polyvinyl chloride resin with various additives such as plasticizers and stabilizers in a certain proportion, and then using processes such as extrusion molding. From the perspective of material properties, the PVC material itself exhibits good chemical stability, can maintain the relative stability of its structure and performance in a complex chemical environment, and resist the erosion of various chemical substances. At the same time, it has a certain corrosion resistance, which makes PVC hose have application potential in scenarios involving the transmission of corrosive media. In addition, PVC material also has certain mechanical properties, can withstand a certain degree of external force, and meet the basic mechanical requirements in different use environments.

[0003] In the actual application process, the performance shortcomings of PVC pipes are gradually emerging. On the one hand, there is room for improvement in its wear resistance, which restricts its application effect under certain specific working conditions, so its wear resistance needs to be improved. On the other hand, the pressure resistance of PVC hoses is also poor. When subjected to high pressure, it is prone to deformation, rupture and other problems. In order to improve the wear resistance and pressure resistance of PVC hoses, one of the commonly used strategies is to add fillers. However, the interface bonding strength between the filler and the PVC substrate is weak. During the use of the pipe, it is affected by external forces, temperature changes and other factors, and has poor stability. At the same time, due to the physical and chemical properties of the filler itself and its interaction with the PVC matrix, the filler is easy to agglomerate in the matrix, which not only leads to uneven local filler concentration, but also makes the wear resistance and pressure resistance effects vary greatly in different parts of the pipe, affecting the overall performance uniformity, but also causes stress concentration, further damaging the comprehensive performance of the PVC hose, greatly limiting the application of PVC hoses in a wider range of fields. Summary of the invention

[0004] In view of the above situation, the present invention aims at the defects of the prior art PVC hose such as poor wear resistance, poor pressure resistance, and problems in the bonding and dispersion of fillers with the PVC substrate. The present invention achieves a significant improvement in the pressure resistance and wear resistance of the PVC hose by performing specific modification treatment on sisal fiber and optimizing the formula composition, while improving the overall performance and processing performance of the material.

[0005] In order to achieve the above-mentioned purpose, the following technical scheme is adopted: The present invention provides a modified resin composition for a high-pressure and high-wear-resistant PVC hose, comprising the following components in parts by weight: 120-150 parts of polyvinyl chloride, 20-40 parts of chlorinated paraffin, 30-50 parts of modified sisal fiber, 6-15 parts of aminosilane coupling agent, 0.5-2.5 parts of filler, 15-20 parts of stearic acid, 5-10 parts of stearic acid monoglyceride, 5-12 parts of calcium zinc stabilizer and 1-4 parts of methyl methacrylate.

[0006] Furthermore, the modified sisal fiber is prepared by the following steps:

[0007] S1, immersing the sisal fiber in a sodium hydroxide solution with a mass concentration of 25% at 20-30° C. for 1-2 hours, taking it out and washing it with water until it is neutral, adding the alkali-treated sisal fiber to deionized water, adding magnesium aluminum spinel fiber, ultrasonic treatment, then taking it out, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 80-120° C. for 6-12 hours to obtain interlaced modified sisal fiber;

[0008] S2, add 12-aminododecanoic acid and 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester to DMF, stir evenly, slowly dropwise add sodium hydroxide solution with a mass concentration of 15%, and stir continuously to ensure that the reaction system is evenly mixed. After the dropwise addition is completed, react at 80-100° C. for 8-12 hours. After the reaction is completed, add dichloromethane to extract after returning to room temperature, combine the organic phases, and remove the solvent under reduced pressure to obtain a long-chain grafting modifier;

[0009] S3, dispersing the interlaced modified sisal fiber in deionized water, adding sodium sulfite, stirring evenly, heating to 50-80°C for reaction for 2-3h, after the reaction is completed, taking out the fiber, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 100-110°C for 6-12h to obtain the surface sulfonated interlaced modified sisal fiber;

[0010] S4. Mix the surface sulfonated interlaced modified sisal fiber and ethanol, heat to 60-70° C., add a long chain grafting modifier, react for 3-5 hours after the reaction is completed, remove the ethanol under reduced pressure, wash with deionized water for multiple times, and dry at 80-120° C. for 6-12 hours to obtain the modified sisal fiber.

[0011] Furthermore, in step S1, the mass ratio of sisal fiber, sodium hydroxide solution, deionized water and magnesium aluminum spinel fiber is 60-80:150-200:10-20.

[0012] Furthermore, in step S2, the mass ratio of 12-aminododecanoic acid, 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, DMF and sodium hydroxide solution is 18-25:24-30:150-250:5-15.

[0013] Furthermore, in step S3, the mass ratio of the modified sisal fiber, deionized water and sodium sulfite is 30-50:180-220:5-10.

[0014] Furthermore, in step S4, the mass ratio of the surface sulfonated interlaced modified sisal fiber, ethanol and long chain grafting modifier is 15-25:140-180:12-18.

[0015] Furthermore, the chlorinated paraffin is a combination of one or more of CP26, CP42, CP50 and CP70.

[0016] Furthermore, the aminosilane coupling agent is one of KH-540, KH-550, KH-602, KH-792 and KH902.

[0017] Furthermore, the filler is one or a combination of nano calcium carbonate, nano talc, nano titanium dioxide and nano carbon black.

[0018] Furthermore, the modified stabilizer is a composition of calcium stearate, zinc stearate, pentaerythritol and acetylacetone in a mass ratio of 3:1.2-2.5:1-1.6:1-1.5.

[0019] Furthermore, the parameters of the ultrasonic treatment in step S1 are: temperature 40-60° C., power 250-300 W, and treatment time 30-50 min.

[0020] The beneficial effects of the present invention are:

[0021] (1) The present invention performs alkali treatment on sisal fiber and interpenetrates it with magnesium aluminum spinel fiber to modify it. The alkali treatment removes impurities on the fiber surface and increases the binding active sites. The high aspect ratio, high strength and modulus of magnesium aluminum spinel fiber greatly improve the performance of PVC pipe after interpenetration. The modified sisal fiber forms a more stable reinforced network structure in the PVC matrix, increases the surface hardness of the pipe, can better withstand friction, reduce wear, and the distance between the fiber molecular chains is increased and the force is weakened, so that the fiber can flexibly disperse the friction force, thereby improving the wear resistance of the overall structure. The magnesium aluminum spinel fiber acts as a support point to share the pressure, prevents the PVC molecular chain from excessive movement and deformation, and can more evenly disperse the stress under pressure, thereby enhancing the pressure resistance of the pipe.

[0022] (2) The long-chain grafting modifier disclosed in the present invention contains a bicyclo[2.2.2]octane structure which is a cage-like structure with high rigidity. A rigid support is inserted into the molecular chain of the modifier, which has a certain steric hindrance effect. When the polymer is subjected to pressure, the bicyclo structure will hinder the movement of the molecular chains when they want to approach each other or move, so that the pressure cannot be concentrated on the molecular chain at a certain point or in a certain direction, but is more evenly distributed between the molecular chains, thereby avoiding the breakage or excessive deformation of the PVC molecular chain caused by excessive local pressure, thereby improving the pressure resistance of the PVC material. At the same time, the coupling effect of methyl formate and aminosilane coupling agent in its structure forms a three-dimensional structure, which limits the excessive movement of the polymer molecular chain. When subjected to force, it can maintain better shape stability and mechanical properties, further improving the pressure resistance and wear resistance of the PVC material.

[0023] (3) After the present invention introduces sulfonic acid groups and long chain grafting modifiers into the surface of the interlaced modified sisal fibers, the hydrophobic and lipophilic properties of the sisal fibers are improved through the long alkane chains, and the compatibility with PVC is enhanced, so that the sisal fibers are more evenly dispersed in the PVC matrix to avoid agglomeration. The evenly dispersed fibers can more effectively resist friction and reduce local wear. Good compatibility helps to form a more stable structure, improve the uniformity of pressure transmission, and enhance the pressure resistance of the pipe. Good compatibility and dispersibility also improve the processing fluidity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The test results of the wear resistance of the PVC hoses of the embodiments and comparative examples of the present invention are as follows;

[0025] Figure 2 The SEM images of the PVC hoses of Example 4 and Comparative Examples 1-3 after friction of the present invention, wherein (a) is Example 4, (b) is Comparative Example 1, (c) is Comparative Example 2, and (d) is Comparative Example 3;

[0026] Figure 3 The figures are the test results of the aging resistance of the PVC hoses of the embodiments and comparative examples of the present invention.

[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0031] Example 1

[0032] A modified resin composition for a high-pressure and high-wear-resistant PVC hose comprises the following components in parts by weight: 120 parts of polyvinyl chloride, 20 parts of chlorinated paraffin, 30 parts of modified sisal fiber, 6 parts of aminosilane coupling agent, 0.5 parts of filler, 15 parts of stearic acid, 5 parts of stearic acid monoglyceride, 5 parts of calcium zinc stabilizer and 1 part of methyl methacrylate.

[0033] The modified sisal fiber is prepared by the following steps:

[0034] S1, immersing the sisal fiber in a sodium hydroxide solution with a mass concentration of 25% at 20°C for 1h, taking it out and washing it with water until it is neutral, adding the alkali-treated sisal fiber to deionized water, adding magnesium aluminum spinel fiber, ultrasonic treatment, then taking it out, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 80°C for 6h to obtain interlaced modified sisal fiber;

[0035] S2, add 12-aminododecanoic acid and 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester to DMF, stir evenly, slowly dropwise add sodium hydroxide solution with a mass concentration of 15%, and stir continuously to ensure that the reaction system is evenly mixed. After the dropwise addition is completed, react at 80° C. for 8 h. After the reaction is completed, add dichloromethane to extract after returning to room temperature, combine the organic phases, and remove the solvent under reduced pressure to obtain a long-chain grafting modifier;

[0036] S3, dispersing the interlaced modified sisal fiber in deionized water, adding sodium sulfite, stirring evenly, heating to 50°C for reaction for 2h, after the reaction, taking out the fiber, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 100°C for 6h to obtain the surface sulfonated interlaced modified sisal fiber;

[0037] S4. Mix the surface sulfonated interlaced modified sisal fiber and ethanol, heat to 60° C., add a long chain grafting modifier, react for 3 hours after the reaction is completed, remove the ethanol under reduced pressure, wash with deionized water for multiple times, and dry at 80° C. for 6 hours to obtain the modified sisal fiber.

[0038] In step S1, the mass ratio of sisal fiber, sodium hydroxide solution, deionized water and magnesium aluminum spinel fiber is 60:150:10; in step S2, the mass ratio of 12-aminododecanoic acid, 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, DMF and sodium hydroxide solution is 18:24:150:5; in step S3, the mass ratio of interlaced modified sisal fiber, deionized water and sodium sulfite is 30:180:5; in step S4, the surface sulfonated The mass ratio of interlaced modified sisal fiber, ethanol and long chain grafting modifier is 15:140:12; the chlorinated paraffin is CP26; the aminosilane coupling agent is KH-540; the filler is nano calcium carbonate; the modified stabilizer is a composition obtained by mixing calcium stearate, zinc stearate, pentaerythritol and acetylacetone in a mass ratio of 3:1.2:1:1; the parameters of ultrasonic treatment in step S1 are: temperature 40°C, power 250W, and treatment time 30min.

[0039] Example 2

[0040] A modified resin composition for a high-pressure and high-wear-resistant PVC hose comprises the following components in parts by weight: 150 parts of polyvinyl chloride, 40 parts of chlorinated paraffin, 50 parts of modified sisal fiber, 15 parts of aminosilane coupling agent, 2.5 parts of filler, 20 parts of stearic acid, 10 parts of stearic acid monoglyceride, 12 parts of calcium zinc stabilizer and 4 parts of methyl methacrylate.

[0041] The modified sisal fiber is prepared by the following steps:

[0042] S1, immersing the sisal fiber in a sodium hydroxide solution with a mass concentration of 25% at 30°C for 2h, taking it out and washing it with water until it is neutral, adding the alkali-treated sisal fiber to deionized water, adding magnesium aluminum spinel fiber, ultrasonic treatment, then taking it out, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 120°C for 12h to obtain interlaced modified sisal fiber;

[0043] S2, add 12-aminododecanoic acid and 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester to DMF, stir evenly, slowly dropwise add sodium hydroxide solution with a mass concentration of 15%, and stir continuously to ensure that the reaction system is evenly mixed. After the dropwise addition is completed, react at 100° C. for 12 hours. After the reaction is completed, add dichloromethane to extract after returning to room temperature, combine the organic phases, and remove the solvent under reduced pressure to obtain a long-chain grafting modifier;

[0044] S3, dispersing the interlaced modified sisal fiber in deionized water, adding sodium sulfite, stirring evenly, heating to 80°C for reaction for 3h, after the reaction is completed, taking out the fiber, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 110°C for 12h to obtain the surface sulfonated interlaced modified sisal fiber;

[0045] S4. Mix the surface sulfonated interlaced modified sisal fiber and ethanol, heat to 70° C., add a long chain grafting modifier, react for 5 hours after the reaction is completed, remove the ethanol under reduced pressure, wash with deionized water for multiple times, and dry at 120° C. for 12 hours to obtain the modified sisal fiber.

[0046] In step S1, the mass ratio of sisal fiber, sodium hydroxide solution, deionized water and magnesium aluminum spinel fiber is 80:200:20; in step S2, the mass ratio of 12-aminododecanoic acid, 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, DMF and sodium hydroxide solution is 25:30:250:15; in step S3, the mass ratio of interlaced modified sisal fiber, deionized water and sodium sulfite is 50:220:10; in step S4, the surface sulfonated interlaced The mass ratio of the inserted modified sisal fiber, ethanol and the long chain grafting modifier is 25:180:18; the chlorinated paraffin is CP42; the aminosilane coupling agent is KH-550; the filler is nano talc; the modified stabilizer is a composition obtained by calcium stearate, zinc stearate, pentaerythritol and acetylacetone in a mass ratio of 3:2.5:1.6:1.5; the parameters of the ultrasonic treatment in step S1 are: temperature 60°C, power 300W, and treatment time 50min.

[0047] Example 3

[0048] A modified resin composition for a high-pressure and high-wear-resistant PVC hose comprises the following components in parts by weight: 130 parts of polyvinyl chloride, 30 parts of chlorinated paraffin, 40 parts of modified sisal fiber, 10 parts of aminosilane coupling agent, 1.5 parts of filler, 16 parts of stearic acid, 8 parts of stearic acid monoglyceride, 7 parts of calcium zinc stabilizer and 2.5 parts of methyl methacrylate.

[0049] The modified sisal fiber is prepared by the following steps:

[0050] S1, immersing the sisal fiber in a sodium hydroxide solution with a mass concentration of 25% at 25°C for 1.5h, taking it out and washing it with water until it is neutral, adding the alkali-treated sisal fiber to deionized water, adding magnesium aluminum spinel fiber, ultrasonic treatment, then taking it out, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 100°C for 10h to obtain interlaced modified sisal fiber;

[0051] S2, add 12-aminododecanoic acid and 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester to DMF, stir evenly, slowly dropwise add sodium hydroxide solution with a mass concentration of 15%, and stir continuously to ensure that the reaction system is evenly mixed. After the dropwise addition is completed, react at 90° C. for 10 h. After the reaction is completed, add dichloromethane to extract after returning to room temperature, combine the organic phases, and remove the solvent under reduced pressure to obtain a long-chain grafting modifier;

[0052] S3, dispersing the interlaced modified sisal fiber in deionized water, adding sodium sulfite, stirring evenly, heating to 70°C for reaction for 2.5h, after the reaction, taking out the fiber, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 105°C for 8h to obtain the surface sulfonated interlaced modified sisal fiber;

[0053] S4. Mix the surface sulfonated interlaced modified sisal fiber and ethanol, heat to 65° C., add a long chain grafting modifier, react for 4 hours after the reaction is completed, remove the ethanol under reduced pressure, wash with deionized water for multiple times, and dry at 100° C. for 10 hours to obtain the modified sisal fiber.

[0054] In step S1, the mass ratio of sisal fiber, sodium hydroxide solution, deionized water and magnesium aluminum spinel fiber is 70:180:15; in step S2, the mass ratio of 12-aminododecanoic acid, 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, DMF and sodium hydroxide solution is 20:26:200:12; in step S3, the mass ratio of interleaved modified sisal fiber, deionized water and sodium sulfite is 40:200:8; in step S4, the surface sulfonated interleaved The mass ratio of modified sisal fiber, ethanol and long chain grafting modifier is 20:160:16; the chlorinated paraffin is CP70; the aminosilane coupling agent is KH-792; the filler is nano titanium dioxide; the modified stabilizer is a composition obtained by calcium stearate, zinc stearate, pentaerythritol and acetylacetone in a mass ratio of 3:1.6:1.2:1.2; the parameters of ultrasonic treatment in step S1 are: temperature 50°C, power 280W, and treatment time 40min.

[0055] Example 4

[0056] A modified resin composition for a high-pressure and high-wear-resistant PVC hose. The difference between this embodiment and embodiment 3 is that: the chlorinated paraffin is a combination of CP26, CP42 and CP50 in a mass ratio of 2:2.5:1; the aminosilane coupling agent is KH90; and the filler is a combination of nano-calcium carbonate, nano-talc, nano-titanium dioxide and nano-carbon black in a mass ratio of 2:2.5:1:3.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 4 is that an equal amount of sisal fiber is used to replace the modified sisal fiber in the components of the modified resin composition, and the rest is the same as Example 4.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 4 is that an equal amount of 5-bromovalerate methyl ester is used to replace 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, and the rest is the same as Example 4.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 4 is that an equal amount of 3-aminopropionic acid replaces 12-aminododecanoic acid, and the rest is the same as Example 4.

[0063] Test Example 1

[0064] PVC hose mechanical properties test

[0065] The mechanical properties of the PVC hoses of the embodiments of the present invention and the comparative examples were tested using a HY-0580 rubber PVC pipe tensile testing machine. The results are shown in the following table.

[0066] As can be seen from Table 1, the present invention performs alkali treatment on sisal fiber and intersperses modification with magnesium aluminum spinel fiber, increases the binding active sites, forms a stable reinforced network structure in the PVC matrix, and improves the tensile strength. After the sisal fiber is modified, a stable reinforced network structure is formed in the PVC matrix, which can better withstand external force stretching, so that the material can have a greater elongation before breaking. The stable reinforced network structure formed by the modified sisal fiber in the PVC matrix can better disperse the impact energy. The double ring structure in the long chain branching modifier is also helpful to improve the impact resistance of the material. After the magnesium aluminum spinel fiber is interspersed and modified, it serves as a support point to share the pressure, and the long chain branching The double ring structure in the modifier and the three-dimensional structure formed by the coupling effect can evenly disperse the stress and enhance the pressure resistance of the pipe. In comparative example 1, the unmodified sisal fiber cannot effectively form such a reinforcing network. Since comparative example 2 does not contain a double ring [2.2.2] octane structure in its structure, when the polymer is subjected to tensile force, it cannot hinder the movement of the molecular chain through the double ring structure and limit the excessive displacement of the molecular chain as in the embodiment. Comparative example 3 uses a short-chain modifier, which cannot effectively form a three-dimensional structure to limit the excessive movement of the polymer molecular chain like a long-chain grafting modifier, resulting in a lower tensile strength. Therefore, the test results of various mechanical properties are lower than those of the comparative example.

[0067] Table 1 Test results of mechanical properties of PVC hose

[0068] ItemTensile strength / MPaElongation at break / %Impact strength / J•m-1Compressive strength / MPa

[0069] Example 182.713238.654.3

[0070] Example 278.513642.548.4

[0071] Example 379.313535.452.5

[0072] Example 481.213837.653.2

[0073] Comparative Example 142.89516.541.5

[0074] Comparative Example 252.110124.347.5

[0075] Comparative Example 355.810828.846.8

[0076] Test Example 2

[0077] PVC hose wear resistance test

[0078] The friction coefficient and wear amount of the PVC hoses of the embodiments of the present invention and the comparative examples in a dry friction environment were tested using an MPX-2000 friction and wear tester. The results are shown in Figure 1 ; The SEM image of the PVC hose after friction is shown in Figure 2 , wherein (a) is Example 4, (b) is Comparative Example 1, (c) is Comparative Example 2, and (d) is Comparative Example 3.

[0079] exist Figure 1 In the embodiment 1-4, the friction coefficient and the wear amount are lower. Figure 2It can be further observed in the SEM image that the friction surface of Example 4 is relatively smooth, without obvious granular protrusions or wear marks, which proves that after the sisal fiber is modified, the fiber forms a more stable reinforced network structure in the PVC matrix. This structure not only increases the surface hardness of the pipe, so that it can better withstand the external force during the friction process, but also changes the molecular chain spacing and interaction force of the fiber, so that the fiber can disperse the friction force more flexibly. When subjected to friction, this uniformly dispersed friction force can avoid local stress concentration, thereby reducing wear and damage to the surface of the material. In contrast, in Comparative Example 1, since the sisal fiber is not modified, it is impossible to form an effective reinforced network structure in the PVC matrix. This results in insufficient hardness of the pipe surface, which cannot effectively resist external force impact during friction, and also cannot evenly disperse the friction force, making local areas susceptible to excessive wear. Therefore, obvious granular wear marks can be seen in the SEM image, showing poor wear resistance. Comparative Example 2 lacks a bicyclic [2.2.2] octane structure in its structure, and cannot effectively disperse stress and resist deformation of the molecular chain during friction, resulting in decreased wear resistance. Comparative Example 3 uses a short-chain modifier, which cannot effectively interact with the sisal fiber and the PVC matrix like the long-chain grafting modifier in the embodiment to form a stable three-dimensional structure to limit excessive movement of the polymer molecular chain and enhance the overall performance of the material.

[0080] Test Example 3

[0081] PVC hose aging resistance test

[0082] Aged at 80°C for 72 hours, the tensile strength and impact strength of the PVC hoses of each embodiment and comparative example after aging were tested. The results are shown in Figure 3 .

[0083] From the test results of tensile strength and impact strength after aging, it can be seen that the modified structure in the embodiment can better maintain the performance of the material after aging. This is because the modified sisal fiber has better compatibility with PVC, the formed structure is more stable, and it can better resist performance degradation during the aging process. In the comparative example, since the sisal fiber is not modified or the modified structure is not as perfect as that in the embodiment, the tensile strength and impact strength of the material cannot be effectively maintained during the aging process as in the embodiment, resulting in a more obvious performance degradation.

[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0085] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A modified resin composition for a high pressure-resistant and high wear-resistant PVC hose, characterized in that: The invention comprises the following components in parts by weight: 120-150 parts of polyvinyl chloride, 20-40 parts of chlorinated paraffin, 30-50 parts of modified sisal fiber, 6-15 parts of aminosilane coupling agent, 0.5-2.5 parts of filler, 15-20 parts of stearic acid, 5-10 parts of stearic acid monoglyceride, 5-12 parts of calcium zinc stabilizer and 1-4 parts of methyl methacrylate; The modified sisal fiber is prepared by the following steps: S1, immersing the sisal fiber in a sodium hydroxide solution with a mass concentration of 25% at 20-30° C. for 1-2 hours, taking it out and washing it with water until it is neutral, adding the alkali-treated sisal fiber to deionized water, adding magnesium aluminum spinel fiber, ultrasonic treatment, then taking it out, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 80-120° C. for 6-12 hours to obtain interlaced modified sisal fiber; S2, add 12-aminododecanoic acid and 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester to DMF, stir evenly, slowly dropwise add sodium hydroxide solution with a mass concentration of 15%, and stir continuously to ensure that the reaction system is evenly mixed. After the dropwise addition is completed, react at 80-100° C. for 8-12 hours. After the reaction is completed, add dichloromethane to extract after returning to room temperature, combine the organic phases, and remove the solvent under reduced pressure to obtain a long-chain grafting modifier; S3, dispersing the interlaced modified sisal fiber in deionized water, adding sodium sulfite, stirring evenly, heating to 50-80°C for reaction for 2-3h, after the reaction is completed, taking out the fiber, washing it with deionized water for several times until the washing liquid is neutral, and drying it at 100-110°C for 6-12h to obtain the surface sulfonated interlaced modified sisal fiber; S4. Mix the surface sulfonated interlaced modified sisal fiber and ethanol, heat to 60-70° C., add a long chain grafting modifier, react for 3-5 hours after the reaction is completed, remove the ethanol under reduced pressure, wash with deionized water for multiple times, and dry at 80-120° C. for 6-12 hours to obtain the modified sisal fiber.

2. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 1, characterized in that: In the step S1, the mass ratio of sisal fiber, sodium hydroxide solution, deionized water and magnesium aluminum spinel fiber is 60-80:150-200:10-20.

3. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 2, characterized in that: In the step S2, the mass ratio of 12-aminododecanoic acid, 4-bromobicyclo[2.2.2]octane-1-carboxylic acid methyl ester, DMF and sodium hydroxide solution is 18-25:24-30:150-250:5-15.

4. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 3, characterized in that: In the step S3, the mass ratio of the modified sisal fiber, deionized water and sodium sulfite is 30-50:180-220:5-10.

5. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 4, characterized in that: In the step S4, the mass ratio of the surface sulfonated interlaced modified sisal fiber, ethanol and the long chain grafting modifier is 15-25:140-180:12-18.

6. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 5, characterized in that: The chlorinated paraffin is a combination of one or more of CP26, CP42, CP50 and CP70.

7. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 6, characterized in that: The aminosilane coupling agent is one of KH-540, KH-550, KH-602, KH-792 and KH902.

8. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 7, characterized in that: The filler is one or a combination of nano calcium carbonate, nano talcum powder, nano titanium dioxide and nano carbon black.

9. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 8, characterized in that: The modified stabilizer is a composition of calcium stearate, zinc stearate, pentaerythritol and acetylacetone in a mass ratio of 3:1.2-2.5:1-1.6:1-1.

5.

10. The modified resin composition for high pressure-resistant and high wear-resistant PVC hose according to claim 9, characterized in that: The parameters of the ultrasonic treatment in step S1 are: temperature 40-60° C., power 250-300 W, and treatment time 30-50 min.

Citation Information

Cited By

  • Non-excavation pipeline local repair material and preparation method thereof

    CN120082149A